The Role of Homeroom Teachers in Instilling Educational Values ​​in Students - Nurhamidah Murotal Nadiroh; Kamaludin Gumilar; Yadi Suryadi (CV. Ksatria Siliwangi, 2025)
This study aims to describe the role of homeroom teachers in instilling educational values ​​in students and identify challenges faced in implementing them in the school environment. This study used a qualitative approach with a descriptive research type. Data were obtained through semi-structured interviews using WhatsApp written messages with two homeroom teachers as informants. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that homeroom teachers play a crucial role not only in academic aspects, but also in fostering attitudes, behavior, and social and emotional development of students. The instillation of educational values ​​is carried out through role models, habituation, a personal approach, and linking values ​​to real situations in everyday school life. The values ​​instilled include discipline, responsibility, honesty, courtesy, cooperation, caring, religiosity, independence, and enthusiasm for learning. The research findings also indicate that the success of instilling values ​​is more influenced by ongoing interaction between homeroom teachers and students than by formal learning methods alone. Obstacles faced by homeroom teachers include differences in student character, family background, and environmental influences outside of school. This study concludes that the role of homeroom teachers who are humane, consistent, and supported by cooperation between the school and family is a key factor in the success of instilling educational values ​​in schools.